Automated Fetal Heart Rate Analysis in Labor: Decelerations and Overshoots - Georgieva, A; Payne, S; Moulden, M; Redman, C (2010)
Electronic fetal heart rate (FHR) recording is a standard way of monitoring fetal health in labor. Decelerations and accelerations usually indicate fetal distress and normality respectively. But one type of acceleration may differ, namely an overshoot that may atypically reflect fetal stress. Here we describe a new method for detecting decelerations, accelerations and overshoots as part of a novel system for computerized FHR analysis (OxSyS). There was poor agreement between clinicians when identifying these FHR features visually, which precluded setting a gold standard of interpretation. We therefore introduced 'modified' Sensitivity (SE°) and 'modified' Positive Predictive Value (PPV°) as appropriate performance measures with which the algorithm was optimized. The relation between overshoots and fetal compromise in labor was studied in 15 cases and 15 controls. Overshoots showed promise as an indicator of fetal compromise. Unlike ordinary accelerations, overshoots cannot be considered to be reassuring features of fetal health. © 2010 American Institute of Physics.